Suicidal Ideation Among Sexual Minority Veterans: Results From the 2005–2010 Massachusetts Behavioral Risk Factor Surveillance Survey - Blosnich, John R. (American Public Health Association, 2012)
Suicide is a public health problem disproportionately associated with some demographic characteristics (e.g., sexual orientation, veteran status). Analyses of the Massachusetts Behavioral Risk Factor Surveillance Survey data revealed that more lesbian, gay, and bisexual (i.e., sexual minority) veterans reported suicidal ideation compared with heterosexual veterans. Decreased social and emotional support contributed to explaining the association between sexual minority status and suicidal ideation. More research is needed about suicide risk among sexual minority veterans; they might be a population for outreach and intervention by the Veterans Health Administration.